Busuu as Online Learning Platform on Vocabulary Learning Motivation and Vocabulary Achievement among Students - Alpino Susanto; Said Nuwrun; Tegor Tegor; Wahyu Azhari; Megah Megah; Sri Yuliani (AL-ISHLAH: Jurnal Pendidikan, 2022)
A robust online learning platform is critical for extending education beyond the classroom and facilitating interactive and individualized learning. Language learning has developed some patterns due to social interactions and independent learning experiences. Vocabulary motivation and achievement are critical components of students' English proficiency. Nonetheless, both variables are recognized as critical by lecturers and students, but receive less attention. The purpose of this study was to examine the effect of Busuu, an online learning platform, on the motivation and achievement of university students in Indonesia when it comes to vocabulary learning. The platform's use as an independent variable, whereas motivation for vocabulary learning and vocabulary achievement, were dependent variables. This study employed a quantitative methodology. Busuu facilitates the learning experience by keeping track of the number of words learned, the level of fluency, and the duration of the learning day. The researchers refer to fluency as the indicator in the study. The questionnaire and test were adapted and modified from previous research on motivation and achievement in vocabulary learning. There were 98 participants. The research discovered that the Busuu online learning platform's performance significantly contributes to the motivation and achievement of vocabulary learners. The study proposes a new model of English learning that incorporates online learning platforms in order to boost students' motivation and vocabulary achievement.